Talaropeptides A-D: Structure and Biosynthesis of Extensively N-methylated Linear Peptides From an Australian Marine Tunicate-Derived Talaromyces sp. - Dewapriya, Pradeep; Khalil, Zeinab G.; Prasad, Pritesh; Salim, Angela A.; Cruz-Morales, Pablo; Marcellin, Esteban; Capon, Robert J. (Frontiers in Chemistry, 2018)
An Australian marine tunicate-derived fungus, Talaromyces sp. CMB-TU011 was subjected to a program of analytical microbioreactor (MATRIX) cultivations, supported by UHPLC-QTOF profiling, to reveal conditions for producing a new class of extensively N-methylated 11-12 residue linear peptides, talaropeptides A-D (2-5). The structures for 2-5, inclusive of absolute configurations, were determined by a combination of detailed spectroscopic and chemical (e.g. C3 and C18 Marfey's) analyses. We report on the biological properties of 2-5, including plasma stability, as well as antibacterial, antifungal and cell cytotoxicity. The talaropeptide mega non-ribosomal peptide synthetase (NRPS) is described, as second only in size to that for the fungus-derived immunosuppressant cyclosporine (an 11-residue extensively N-methylated cyclic peptide).